Integration Bioprocess of B-Phycoerythrin and Exopolysaccharides Production From Photosynthetic Microalga Porphyridium cruentum - Yin, Hao-Chan; Sui, Ji-Kang; Han, Tian-Li; Liu, Tian-Zhong; Wang, Hui (Frontiers in Marine Science, 2022)
Red microalga Porphyridium cruentum has great potential for converting CO2 into high-value bioactive compounds, such as B-phycoerythrin (B-PE) and extracellular polysaccharides or exopolysaccharides (EPS). This study aimed to establish the integration bioprocess of B-PE and EPS production from P. cruentum. First, different kinds of growth medium and CO2 concentration were assessed indoor in terms of high biomass and B-PE and EPS contents. As follows, P. cruentum cells were outdoor scale-up cultured in 700 L pressurized tubular reactors for 9 days till the biomass reached 0.85 g/L and then separated from supernatants via centrifugation. Three different methods were adopted to extract phycobiliproteins, and the highest PE contents were extracted from cells by repeated freeze-thawing treatment along with the optimization of significant variables, and finally, 7.99 mg/L B-PE (16,500 Da) with a purity index of 0.82 was obtained. Moreover, analysis of physicochemical properties of EPS extracted from P. cruentum showed that the sulfate content was 14.85% and the uronic acid content was 9.36%.